Contingency Planning in Traditional and Islamic Banks During the Crisis in Syria: Crisis Management Perspective - Kahwaji, Ahmad Taha (European Journal of Islamic Finance, 2018)
The Syrian crisis is one of the worst crisis in the world. It has dramatically affected many aspects of life and civilization. It imposed millions of emigration to many countries, and negatively affected the national economy including international companies operating in Syria, and also local. It imposed on its economic sides the exit of many institutions and companies from the market, and also led to the adoption of different types of retrenchment strategies by companies that could not exit or those who wanted to stay challenged and motivated by the management of its operations and activities in an exceptional manner commensurate with the crisis continues to the present. Before the Syrian crisis, banking industry (Traditional and Islamic) in Syria was growing rapidly and in a stable pace. The crisis situation has resulted an unexpected conditions that banks were have to deal with. This research highlights the negative effects of the crisis on Islamic and traditional banks operated in Syria, it also indicates some of the responses the banks has employed in order to mitigate or eliminate the crisis bad effects. The applied research has been modified to explore implementation of crisis management literature in Syrian banks (Traditional and Islamic) and the role of that implementation in supporting contingency planning. The study found three main results. First, there is a positive and significant correlation between the crisis management and contingency planning. Second, the Syrian employees believe that Syrian banks has adapted crisis management practices. Finally, the study indicated that banks’ employee believe that their work conditions and job environment was negatively affected by the crisis situation.